2018
DOI: 10.1016/j.biopsych.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

TAR DNA-Binding Protein 43 and Disrupted in Schizophrenia 1 Coaggregation Disrupts Dendritic Local Translation and Mental Function in Frontotemporal Lobar Degeneration

Abstract: Our findings reveal a novel role of the aggregate-prone TDP-43/DISC1 protein complex in regulating local translation, which affects aberrant behaviors relevant to multiple psychiatric dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 62 publications
(85 reference statements)
0
23
0
Order By: Relevance
“…TDP-43 aggregates are the most common forms of neuropathological abnormalities in FTD, and animal models with mutation in the gene encoding this protein (TARDBP) are important tools to help understand the role of this protein in behavioral symptoms of FTD. Indeed, TDP-43 was found to co-aggregate with the disrupted in schizophrenia 1 (DISC1) protein in the cytosol of neurons in brains of both FTLD mouse model and patients (Endo et al, 2018). Examination of the animal data revealed that, co-aggregation of TDP-43/DISC1 reduced synaptic protein expression by disrupting activity-dependent dendritic local translation.…”
Section: Neuropathology Of Frontotemporal Dementiamentioning
confidence: 99%
“…TDP-43 aggregates are the most common forms of neuropathological abnormalities in FTD, and animal models with mutation in the gene encoding this protein (TARDBP) are important tools to help understand the role of this protein in behavioral symptoms of FTD. Indeed, TDP-43 was found to co-aggregate with the disrupted in schizophrenia 1 (DISC1) protein in the cytosol of neurons in brains of both FTLD mouse model and patients (Endo et al, 2018). Examination of the animal data revealed that, co-aggregation of TDP-43/DISC1 reduced synaptic protein expression by disrupting activity-dependent dendritic local translation.…”
Section: Neuropathology Of Frontotemporal Dementiamentioning
confidence: 99%
“…In addition, several recent studies have highlighted the importance of proper translational control in regulating behaviours associated with neuropsychiatric and mood disorders [29,30,31]. Trinh and colleagues [30] demonstrated that the disruption of translational regulation by a brain-specific deficiency of PKR-like ER kinase (PERK) resulted in impaired behavioural flexibility among other behavioural deficits.…”
Section: Translational Dysregulation In Neurological Disordersmentioning
confidence: 99%
“…Taken together, these data imply that disturbed local mRNA translation contributes to pathology of ALS. It is worthy to note that TDP-43 is also crucial for regulating dendritic local translation in response to neuronal activity (Endo et al, 2018). This may suggest the role of TDP-43 for psychiatric outcomes observed in FTD patients.…”
Section: Amyotrophic Lateral Sclerosis (Als) and Frontotemporal Demenmentioning
confidence: 93%